Studies on prosody and autism by an acoustic analysis approach: a narrative review - Lisboa, Leandro; Roberto, Tania Mikaela Garcia (Journal of Speech Sciences, 2023)
This review, linked to Núcleo de Estudos sobre Prosódia e Ensino de Língua (NEPEL//UFRRJ), is dedicated to the data survey of scientific material published under the theme autism and prosody in the last decade. This paper aims to collect published papers under the topic mentioned in which present as methodological approach the acoustic analysis, in a time frame from 2011 to 2020/2021. Thereunto, specific keywords were selected, along with the usage of boolean operators for the research in 6 different index platforms: ERIC, PsycINFO, PubMed, MLA, SciELO and Scopus. As the research progressed, 174 articles were collected. Afterwards, we tabbed the data into different categories, of which resulted in 74 relevant articles. Finally, with the analysis completed, we pointed both comparative and contrasting aspects from those researched papers and concluded that the papers published under the theme of Autism Spectrum Disorder and prosody are scarce in quantity. Thence, we also aimed to report possible alternatives and to lead future research into the theme of autism and prosody, using the acoustic analysis as its approach.